The effect of bonus compensation, profitability, liquidity, and firm size on earnings management on food and beverage companies registered in IDX - Maulidyah, Mia Nur; Susilo, Dwi Ermayanti (Enrichment : Journal of Management, 2023)
The purpose of this research is to discover whether bonus compensation, profitability, liquidity, and firm size to earnings management in food and beverage sub-sector companies that have sharia shares on the idx in period 2020 – 2022. This research uses a purposing sampling method. The data used in this research is secondary data originating from financial report. The population of this research is 32 companies including 14 ordinary shares and 18 sharia shares. The sample used in this research was 18 compnies with 54 data in the 2020 – 2022 period. The method used in this research is a quantitative method with multiple linier reggression analysis techniques. The result of this research is: (1) bonus compensation has no effect on earnings management. (2) profitability has a positive and significant effect on earnings management. (3) liquidity has no effect on earnings management. (4) firm size has a negative and significant effect on earnings management. Conclusion simultaneously bonus compensation, profitability, liquidity, and firm size have an effect on earnings management. Partially the variables profitability and firm size have an effect on earnings management and variables bonus compensation and liquidity has no effect on earnings management